Fisiologia da motilidade colônica e da evacuação, treinamento esfincteriano anal e distúrbios funcionais da evacuação - Miranda, José Eduardo Gomes Bueno de; Carvalho, Mary de Assis [UNESP]; Machado, Nilton Carlos [UNESP] (My University, 2011)
Chronic constipation is among the ten most common problems in pediatric practice. Thus, the high prevalence of constipation and hence the work burden for the Pediatrician require a more detailed training. Therefore the understanding of the physiological mechanisms of fecal continence, the normal process of evacuation and bowel toilet training are essential for the proper care of these patients and will allow achieving better results withthesechildren.

A constipação crônica está entre os dez problemas mais frequentes na prática pediátrica. Assim, a alta prevalência da constipação e, consequentemente, da carga de trabalho para o pediatra exigem um treinamento mais detalhado. Portanto, a compreensão dos mecanismos fisiológicos que regem os controlesdacontinênciafecal,oprocessonormaldaevacuação eotreinamentoesfincterianoanalsãofundamentaisparaobom atendimento desses pacientes e permitirão obter uma melhor resolutividadecomessascrianças.
Physiology of colonic motility and defecation, bowel toilet training and functional disorders of defecation
Keywords: Constipation; Defecation; Anal canal; Toilet training; Constipação intestinal; Defecação; Canal anal|Treinamento no uso de toaletes